High-strength high-temperature-resistant inorganic coating and use method thereof

By optimizing the inorganic coating formulation and process, a high-strength and thermal stability coating is formed, which solves the problem of insufficient adhesion of inorganic heat-proof coatings under high temperature and mechanical stress, and ensures the protective performance of high temperature environments.

CN119242083APending Publication Date: 2025-01-03BEIJING LINGKONG TIANXING TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411641461.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing inorganic heat-proof coatings are prone to peeling and cracking during transportation and storage, and have insufficient strength and are difficult to maintain adhesion under high temperature and mechanical stress, resulting in the substrate being exposed to a high temperature environment and losing its heat protection function.

Method used

Using inorganic coating formulas including dimensional fillers, thermal insulation fillers, silicates, metal oxides and silica sols, the high-strength and good thermal stability coating is formed by optimizing the raw material ratio and process flow. After the coating is cured, it will be used to form a coating with high strength and good thermal stability. Heat at medium and high temperatures to enhance adhesion and wear resistance.

Benefits of technology

The high-strength adhesion and thermal stability of the coating are achieved, the problem of vulnerability in coating transportation and construction is solved, and the protection performance is ensured in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a high-strength high-temperature-resistant inorganic coating and a use method thereof. Relates to the field of high-temperature-resistant coatings. Comprising the following raw materials in parts by weight: 20-40 parts of vitamin type filler, 1-15 parts of heat-insulating filler, 30-40 parts of silicate, 5-20 parts of metal oxide and 90-150 parts of silica sol. The strength of the inorganic coating reaches 7 MPa or above, the adhesive force of the coating is high, and the problem that the coating is prone to damage in the transportation process and construction is solved. The coating can be cured at normal temperature and is convenient to construct.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high temperature resistant coatings, and in particular to a high strength high temperature resistant inorganic coating and a use method thereof. Background Art

[0002] Thermal protection coatings effectively protect the substrate by reflecting thermal radiation, reducing heat conduction, and lowering surface temperature. They are widely used in high-temperature environments such as the outer surface of rockets to ensure that the rocket cabin has a good temperature environment for normal operation and normal flight during flight.

[0003] According to its composition and function, heat-resistant coatings are mainly divided into organic heat-resistant coatings and inorganic heat-resistant coatings. Among them, organic heat-resistant coatings have excellent chemical corrosion resistance, good flexibility, and are easy to apply on surfaces of complex shapes, but their high temperature resistance is relatively poor. They can usually only withstand temperatures of 200~300℃. Long-term exposure to high temperatures will cause thermal degradation, resulting in performance degradation. Inorganic heat-resistant coatings have much higher high temperature resistance than organic heat-resistant coatings. They can withstand temperatures up to 1200℃ or even higher and remain stable at high temperatures. They are suitable for scenes such as high-temperature equipment. At the same time, inorganic heat-resistant coatings also have the advantages of good chemical stability, high hardness and wear resistance, safety and environmental protection, good adhesion, and fire retardancy.

[0004] However, at present, the strength of inorganic heat-resistant coatings is mostly between 1 and 2 MPa, and some are even lower than 1 MPa. They are prone to bumps during transportation and storage, and the coatings are prone to peeling and cracking. Under the action of high temperature and mechanical stress, coatings with insufficient strength are difficult to adhere firmly to the surface of the substrate. Once peeled or cracked, the substrate will be directly exposed to the high temperature environment and lose its heat protection function. Moreover, if the peeling area is too large, it will cause the aerodynamic shape to change, which will in turn affect the aerodynamic thermal environment, affect the flight status, and cause immeasurable losses. Summary of the invention

[0005] In view of the technical problems existing in the prior art, the present invention aims to provide a high-strength, high-temperature-resistant inorganic coating and a method for using the same. One of the purposes of the present invention is to provide a high-strength, high-temperature-resistant inorganic coating, the inorganic coating comprising the following raw materials in parts by weight: 20~40 parts of dimensional filler 1~15 parts of thermal insulation filler 30~40 parts of silicate Metal oxide 5~20 parts 90~150 parts of silica sol.

[0006] Preferably, the mass ratio of the silicate to alumina is 2-6:1, and the mass ratio of the silicate to silica sol is 1:2.5-4.2.

[0007] Preferably, the dimensional filler includes one or more of mullite fiber, chopped quartz fiber powder or chopped glass fiber powder.

[0008] Preferably, the particle size of the dimensional filler is 10-50 um.

[0009] Preferably, the thermal insulation filler includes one or more of expanded perlite, expanded vermiculite, hollow glass microspheres, hollow phenolic microspheres or silica aerogel.

[0010] Preferably, the thermal insulation filler has a density of 0.25-0.6 g / cm³, a compressive strength of 10-40 MPa, and an average particle size of 10-50 um. Preferably, the purity of the metal oxide is above 99 wt %, and the flake diameter is 10-50 um.

[0011] Preferably, the metal oxide includes one or more of aluminum oxide, magnesium oxide or zirconium oxide.

[0012] A second object of the present invention is to provide a method for using a high-strength, high-temperature resistant inorganic coating, the method comprising: The materials are mixed in proportion, stirred evenly and then coated on the surface of the object. After the coating is cured, it is heated at 600℃~800℃ for 1~3h to obtain a high-strength and high-temperature resistant inorganic coating.

[0013] Preferably, the coating curing temperature is 20° C. to 60° C., the curing time is 18 h to 30 h, and the coating thickness is 0.8 mm to 1.5 mm.

[0014] Beneficial effects of the present invention: The inorganic coating provided by the present invention has a strength of more than 7MPa and strong coating adhesion, which solves the problem of coating fragility during transportation and construction. It has excellent thermal stability, can be cured at room temperature, and is easy to construct. DETAILED DESCRIPTION

[0015] According to the first aspect of the present invention, a high-strength and high-temperature resistant inorganic coating is provided, wherein the inorganic coating comprises the following raw materials in parts by weight.

[0016] 20~40 parts of dimensional filler 1~15 parts of thermal insulation filler 30~40 parts of silicate 5 to 20 parts of metal oxide, and 90~150 parts of silica sol.

[0017] In the present invention, the weight of the dimensional filler is, for example, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts.

[0018] In the present invention, the weight of the thermal insulation filler is, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 12 parts, 13 parts, 14 parts or 15 parts.

[0019] In the present invention, the weight of the silicate is, for example, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts.

[0020] In the present invention, the weight of the metal oxide is, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.

[0021] In the present invention, the weight of the silica sol is, for example, 90 parts, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts or 150 parts.

[0022] In a preferred embodiment of the present invention, the mass ratio of the silicate to alumina is 2-6:1, and the mass ratio of the silicate to silica sol is 1:2.5-4.2.

[0023] In the present invention, the mass ratio of silicate to silica sol is 1:2.5~4.2 in order to ensure good film-forming properties. Silica sol plays a key bonding and filling role in the film-forming process, and it contains a large amount of silanol groups (-Si-OH). Both alumina and aluminum silicate can react with the silanol groups (-Si-OH) in silica sol. When the mass ratio of silicate to silica sol is within this range, the silicate can fully react with the silanol groups in the silica sol and participate in the film formation process. If the silicate content is too high, that is, the mass ratio is greater than 1:2.5, it may cause the reaction to be too violent, making the gel time of the coating too short, which is not conducive to construction operations, and may make the structure of the film too dense and the flexibility decreased. On the contrary, if the silicate content is too low, the mass ratio is less than 1:4.2, then there are fewer silicates participating in the film-forming reaction, and a sufficiently dense network structure may not be formed, resulting in a decrease in the adhesion, water resistance and other properties of the coating.

[0024] The aluminum atoms in alumina have empty orbitals and can form coordination bonds with the oxygen atoms in the silanol groups. Aluminum silicate, on the other hand, contains Si-Al bonds in its structure, and the silicon atoms in it can also react with silanol groups. This dual reaction mechanism enables the coating to form a more complex and highly cross-linked network structure when forming a film. The reaction of alumina can form Al-O-Si connections in local areas, and the participation of aluminum silicate further expands this connection, making the molecular network of the coating more compact and stable, just like in a building structure, different types of connectors are used at the same time to reinforce the frame. The particles of alumina and aluminum silicate also play a physical filling role in the coating. Alumina usually has a higher hardness and density, and it can fill the gaps between aluminum silicate particles, and vice versa. This mutual filling makes the microstructure of the coating denser and reduces the presence of pores. Under the action of external stress, the mutual support between the particles is enhanced, which can better resist deformation. When the coating is subjected to tensile or compressive stress, these closely arranged particles can effectively disperse the stress, prevent cracks or damage in the coating, and thus improve the structural stability of the coating.

[0025] When the mass ratio of silicate to alumina is in the range of 2 to 6:1, sufficient silicate can be provided to synergistically enhance the strength of the coating with alumina. Silicate can react with alumina during the film formation process of the coating, and at the same time, it will also undergo polycondensation and other reactions to form a complex network structure. If the silicate content is too low, the cross-linked structure formed by the reaction with alumina is limited, and the alumina particles cannot be effectively wrapped and fixed, resulting in insufficient coating strength. For example, when the mass ratio is higher than 1:1, the alumina particles may be unevenly dispersed in the coating, local stress concentration may occur, and the coating may easily crack when subjected to external force. On the other hand, if the silicate content is too high, relative to alumina, the rigid structure of the coating will be overly dependent on the silicate's own network, and the reinforcing effect of alumina cannot be fully exerted. Because alumina has high hardness and strength, an appropriate amount of alumina can be used as a reinforcing phase to improve the mechanical properties of the coating. When the mass ratio exceeds 6:1, the hardness and impact resistance of the coating may decrease.

[0026] Alumina has a high melting point (about 2072°C) and thermal stability, and aluminum silicate also shows good stability at high temperatures. In high-temperature environments, they work together to maintain the structure of the coating. Alumina can serve as a "thermal stability core", and its crystal structure can withstand large thermal stresses at high temperatures without significant deformation. Aluminum silicate surrounds the alumina and further enhances the overall thermal stability of the coating through its own high-temperature resistance. At the same time, the chemical bonds formed by their reaction with silica sol can also maintain a certain strength at high temperatures, preventing the coating from softening or peeling off at high temperatures. For example, in the coating application of a high-temperature furnace, this synergistic effect can ensure that the coating works for a long time in a high-temperature environment without failure.

[0027] From the perspective of thermal insulation, the composite structure of alumina, aluminum silicate and expanded perlite hollow glass microspheres can effectively hinder the transfer of heat. The complex microstructure they form in the coating increases the path length and thermal resistance of heat conduction. The particle interface of alumina powder and aluminum silicate powder will reflect and scatter part of the heat. Hollow glass microspheres can reduce density and thermal conductivity, and complement alumina, so that while the strength increases, the density and thermal conductivity will not increase significantly. The internal molecular structure of expanded perlite, aluminum silicate and silica sol can effectively reduce the efficiency of heat conduction.

[0028] Under high temperature environment, the appropriate mass ratio of the two can form a good thermally stable structure. If there is too little silicate, it may not be able to effectively fill the gaps between alumina particles at high temperature, resulting in problems such as inconsistent thermal expansion of the coating, which damages the coating structure. When there is too much silicate, due to its own thermal expansion coefficient and other factors, it may generate excessive internal stress at high temperature, affecting the overall structure of the coating.

[0029] In addition, the high hardness of aluminum oxide makes it play an important role in improving the wear resistance of the coating. Aluminum silicate can enhance the toughness of the coating surface through its close combination with aluminum oxide. When the coating is subjected to friction or wear, the aluminum oxide particles can resist wear, and the presence of aluminum oxide can prevent the aluminum silicate particles from falling off. Because aluminum silicate has low strength and aluminum oxide has high strength, aluminum oxide protects aluminum silicate, so that the coating can maintain good wear resistance.

[0030] In a preferred embodiment of the present invention, the dimensional filler includes one or more of mullite fiber, chopped quartz fiber powder or chopped glass fiber powder.

[0031] In the present invention, the dimensional filler is, for example, mullite fiber, chopped quartz fiber powder, chopped glass fiber powder, mullite fiber and chopped quartz fiber powder, chopped quartz fiber powder and chopped glass fiber powder, or a combination of mullite fiber, chopped quartz fiber powder and chopped glass fiber powder.

[0032] In the present invention, the dimensional filler is preferably mullite fiber.

[0033] In a preferred embodiment of the present invention, the particle size of the dimensional filler is 10-50 um.

[0034] In the present invention, the particle size of the dimensional filler is 10-50um, which is beneficial to improve the strength of the coating. First, fillers in this particle size range can achieve a good filling effect in the coating. They are moderate in size and can be evenly filled in the gaps between the molecules of the coating matrix, making the coating microstructure more compact, just like tiny "building blocks" filling the gaps and enhancing the overall tightness. Secondly, when the coating is subjected to external force, these filler particles can act as stress dispersion points to disperse the concentrated stress to a larger area, avoiding local stress concentration leading to coating rupture, just like small pillars in a force-bearing structure disperse pressure, making the coating more stable.

[0035] In a high temperature environment, the thermal expansion coefficient of filler particles in this size range can be well matched with that of the coating matrix. If the particle size is too large, the difference in thermal expansion or contraction is large, which can easily generate internal stress and cause cracks or peeling in the coating. Filler particles of 10-50μm can cooperate with the matrix during thermal changes to reduce internal stress and maintain the integrity of the coating structure at high temperatures. On the other hand, these filler particles help improve thermal insulation performance. The microstructure formed in the coating increases the length of the heat transfer path. Expanded perlite and hollow glass microspheres are equivalent to a frame structure with air inside the structure. Due to the low thermal conductivity of air (0.0244W / m·K), the overall thermal conductivity of the coating decreases. This makes heat conduction more difficult, such as in high-temperature furnace equipment coating applications, which can effectively block heat transfer and protect the internal structure.

[0036] During the coating preparation process, fillers with this particle size have good dispersibility. If the particle size is too small, it is easy to crack during the curing process due to the intermolecular force, and if the particle size is too large, it is easy to settle. However, fillers with 10-50μm are easy to disperse evenly during stirring and mixing operations, ensuring consistent and stable coating performance. At the same time, it can make the coating have suitable rheological properties, adjust the viscosity and fluidity of the coating, prevent sagging and facilitate construction, and ensure good integrity and integrity after curing, ensuring that the coating is smoothly applied during construction and forms a uniform and smooth coating.

[0037] In a preferred embodiment of the present invention, the thermal insulation filler includes one or more of expanded perlite, expanded vermiculite, hollow glass microspheres, hollow phenolic microspheres or silica aerogel.

[0038] In the present invention, the thermal insulation filler is, for example, expanded perlite, expanded vermiculite, hollow glass microspheres, hollow phenolic microspheres, silica aerogel, hollow glass microspheres and expanded perlite, expanded vermiculite and hollow glass microspheres, hollow glass microspheres and hollow phenolic microspheres, or hollow glass microspheres, expanded perlite and expanded vermiculite.

[0039] In the present invention, the thermal insulation filler is preferably hollow glass microspheres.

[0040] In a preferred embodiment of the present invention, the thermal insulation filler has a density of 0.2-0.6 g / cm³, a compressive strength of 10-55 MPa, and an average particle size of 10-50 um.

[0041] In a preferred embodiment of the present invention, the purity of the metal oxide is above 99 wt % and the particle size is 10-50 um.

[0042] Preferably, the metal is oxidized into a spherical shape.

[0043] In the present invention, metal oxides can be used as reinforcing phases to improve the strength of the coating. After the coating is cured, the metal oxide particles are evenly dispersed in the coating matrix, and when the coating is subjected to external forces, these particles can bear part of the stress. For example, under tensile or compressive stress, the metal oxide particles are like tiny "support skeletons", which disperse the stress to a larger area through interaction with the matrix, thereby enhancing the tensile and compressive strength of the coating. At the same time, the metal oxide particles can also prevent the expansion of cracks. When tiny cracks appear in the coating, the cracks will encounter metal oxide particles during the expansion process. Due to the obstruction of the particles, the expansion direction of the cracks will change or be terminated, which helps to maintain the integrity of the coating and improve the strength of the coating.

[0044] In high temperature environments, metal oxides can maintain their own structural stability and will not soften or decompose like some organic materials. They form a thermally stable "skeleton" structure in the coating, allowing the coating to maintain a certain shape and performance at high temperatures. For example, in the lining coating of a high-temperature furnace, metal oxides can effectively resist high-temperature thermal radiation and thermal convection, preventing the coating from failing due to high temperatures. In addition, the presence of metal oxides can also reduce the thermal expansion coefficient of the coating, reduce the internal stress of the coating caused by thermal expansion at high temperatures, and further improve the high-temperature resistance of the coating.

[0045] Metal oxides usually have a certain tolerance to chemicals such as acids and alkalis. When the coating is applied in some chemically corrosive environments, metal oxides can act as a chemical barrier. They can prevent or slow down the erosion of the coating substrate by chemicals, thereby extending the service life of the coating. For example, in the protective coating of chemical equipment, metal oxides can resist the corrosion of chemical reagents such as acids and alkalis, protecting the surface of the equipment from damage.

[0046] High-purity metal oxides can ensure the stable performance of their own properties. If the purity of the metal oxide is low, the impurities contained in it may have an adverse effect on its performance. For example, impurities may reduce the melting point, thermal stability or chemical stability of the metal oxide. In a high temperature environment, impurities may react first, resulting in defects in the coating or reduced performance. Metal oxides with a purity of more than 99wt% can minimize the interference of impurities and ensure stable and reliable performance in enhancing coating strength, improving temperature resistance and chemical stability.

[0047] In the process of coating preparation, high-purity metal oxides can be more compatible with the coating matrix. High-purity metal oxides have relatively more surface active sites, and can form a stronger bond when chemically reacting or physically adsorbing with the matrix material or other additives. For example, after mixing with binders such as silica sol, high-purity metal oxides can work more effectively to form a tighter network structure, thereby improving the performance of the coating.

[0048] Metal oxide particles with a particle size of 10-50μm are moderate in size and can play a good filling role in the coating. They can fill the gaps between the coating matrix to make the microstructure of the coating more compact. If the particle size is too small and the number of particles is too large, cracking is likely to occur during the curing process; if the particle size is too large, the gaps between the particles will increase, not only will it be impossible to spray, but it will also be unfavorable to form a compact coating structure. For example, during the drying or curing process of the coating, particles of 10-50μm can act like "fillers" to make the volume of the coating more substantial and improve the density and strength of the coating.

[0049] Metal oxide particles in this size range help disperse stress and enhance coating strength. When the coating is subjected to external forces, the particles can serve as stress dispersion nodes. Stress is transferred from the substrate to the particles. Since the particles have a certain size and strength, they can disperse the stress to the surrounding substrate material to avoid stress concentration at a certain point that causes coating damage. Moreover, the appropriate particle size can ensure that the particles have enough contact area in the coating to interact with the substrate, thereby better playing its role in enhancing strength.

[0050] Spherical metal oxides have better fluidity and dispersibility in coatings. During the preparation and application of coatings, the friction between spherical particles is relatively small, making it easier to disperse evenly in the coating system. Compared with other irregularly shaped particles, spherical particles can move more smoothly in the coating during stirring, spraying or brushing, thereby ensuring their uniform distribution in the coating. This is very important for forming a coating with uniform performance, because evenly distributed metal oxide particles can play the same reinforcing role throughout the coating. The spherical morphology can also reduce stress concentration. When the coating is subjected to external forces, the contact between the spherical metal oxide particles and the substrate is relatively uniform, and the stress is more evenly distributed around the particles. Irregularly shaped particles may cause stress concentration at some sharp corners, making the coating more prone to cracks or damage in these areas. Therefore, spherical metal oxide particles can better withstand and disperse stress, which is beneficial to improving the strength and stability of the coating.

[0051] In a preferred embodiment of the present invention, the metal oxide includes one or more of aluminum oxide, magnesium oxide or zirconium oxide.

[0052] In the present invention, the metal oxide is preferably aluminum oxide. Spherical aluminum oxide has a relatively low thermal conductivity and high strength, and is more suitable for high temperature resistant and low thermal conductivity materials.

[0053] According to the second aspect of the present invention, a method for using a high-strength, high-temperature resistant inorganic coating is provided, the method comprising: The materials are mixed in proportion, stirred evenly and then coated on the surface of the object. After the coating is cured, it is heated at 600℃~800℃ for 1h~3h to obtain a high-strength and high-temperature resistant inorganic coating.

[0054] In a preferred embodiment of the present invention, the coating curing temperature is 20°C to 60°C, the curing time is 18h to 30h, and the coating thickness is 0.8mm to 1.5mm.

[0055] In the present invention, the coating method includes spraying or knife coating, preferably spraying.

[0056] In the present invention, the heating temperature is, for example, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, or 800°C.

[0057] In the present invention, during the curing process, since silica sol is a film-forming material that dries at room temperature, the film-forming process involves the silanol group of colloidal silica (-Si-OH) reacting with the substrate and aluminum silicate, aluminum oxide and other substances in the coating to form strong bonding and adhesion. After the silica sol forms a film, a network structure is formed. Once formed, this structure will no longer dissolve, so it has excellent water resistance, weather resistance and high temperature resistance.

[0058] Alumina and aluminum silicate are added to silica sol as fillers. During the film-forming process, alumina and aluminum silicate can react with the silanol groups in the silica sol to further enhance the structural stability and durability of the coating. At the same time, the addition of alumina and aluminum silicate can also improve the thixotropy and suspension of the silica sol, making it more stable and easy to operate during the construction process.

[0059] In the present invention, the formula raw materials are pure inorganic materials. After the coating is cured, heating at 600°C to 800°C will not affect the material properties. During the high-temperature heating process, the silicon dioxide particles in the silica sol can be interconnected with the silicon-oxygen tetrahedral structure in the silicate, further improving the network structure of the coating and further enhancing the hardness of the coating.

[0060] When heated, silicates undergo a dehydration condensation reaction. Taking aluminosilicate as an example, at high temperatures, the water molecules in its structure are released, and the coordination structure around aluminum ions and silicon ions is adjusted. It chemically bonds with the active groups on the surface of the mullite fiber. The main component of mullite fiber is mullite (3Al2O3·2SiO2), and the Al-OH and Si-OH groups on its surface can interact with the silicon-oxygen bonds and aluminum-oxygen bonds in silicates. This chemical bonding allows the mullite fiber to be tightly bonded to the silicate, enhancing the internal connection of the coating.

[0061] Silicates also interact with the silicon-oxygen structure on the surface of hollow glass microspheres at high temperatures. The main components of hollow glass microspheres are silicon dioxide, etc., and the Si-O-Si bonds of silicates and silica sols fill the gaps between the hollow glass microspheres and the coating matrix, reducing the thermal conductivity of the coating. At high temperatures, the alumina particles in the coating and the alumina in the mullite fibers will form a certain solid solution structure. The formation of this structure can improve the toughness and strength of the material and prevent the expansion of cracks in the coating. When the coating expands or contracts due to heat, the mullite fibers can disperse the stress through the friction and chemical bonding between the fibers and the matrix. And the mullite fibers will also be intertwined to form a reinforced network. This network structure can evenly disperse the stress in the coating to the entire coating system, prevent the coating from being damaged due to local stress concentration, and thus improve the strength of the coating. As the temperature rises, the hollow glass microspheres will soften to a certain extent. The softened hollow glass microspheres can better fill the pores and tiny cracks in the coating. The difference in thermal expansion coefficients between the hollow glass microspheres and other components also plays a positive role at high temperatures. When the coating expands due to heat, the expansion of the hollow glass microspheres can be coordinated with the other components to avoid excessive internal stress caused by mismatched thermal expansion coefficients. At the same time, the hollow glass microspheres can also reflect some heat, reducing the thermal stress generated by the temperature gradient inside the coating, thereby improving the strength of the coating at high temperatures.

[0062] Example The present invention provides 9 embodiments and 5 comparative examples. Table 1 shows the raw material ratios of embodiments 1 to 7 and comparative examples 1 to 4. The dimensional filler used in embodiments 1 to 9 and comparative examples 1 to 5 is mullite fiber, with a weight of 30 parts; the heat insulating filler is hollow glass microspheres, with a weight of 8 parts; the silicate uses aluminum silicate, and the metal oxide uses aluminum oxide.

[0063] The other raw material proportions of Examples 1 to 7 and Comparative Examples 1 to 4 are shown in Table 1.

[0064] Table 1 Raw material ratios of Examples 1 to 7 and Comparative Examples 1 to 4

[0065] The specific preparation method is: The materials are mixed in proportion, stirred evenly and then sprayed on the surface of the object. After the coating is cured, it is heated at 700°C for 2 hours to obtain a high-strength and high-temperature resistant inorganic coating.

[0066] The coating in Comparative Example 2 cracked after curing and heating, the coating in Comparative Example 3 had severe sagging, and the coating in Comparative Example 4 was uneven and easily sank to the bottom.

[0067] Example 8 The coating formula is consistent with that in Example 3. After being stirred evenly, it is sprayed on the surface of the object. After the coating is cured, it is heated at 600° C. for 2 h to obtain a high-strength and high-temperature resistant inorganic coating.

[0068] Example 9 The coating formula is consistent with that in Example 3. After being stirred evenly, it is sprayed on the surface of the object. After the coating is cured, it is heated at 800° C. for 2 h to obtain a high-strength and high-temperature resistant inorganic coating.

[0069] Comparative Example 5 The coating formula is consistent with that in Example 3. After being stirred evenly, it is sprayed on the surface of the object and is not subjected to high-temperature heating after curing.

[0070] Performance Testing Compression test standard: GB / T17671-1999 Thermal conductivity test standard: GB / T 32064-2015 Table 2 Test results of Examples 1 to 9 and Comparative Examples 1 to 5

Claims

1. A high-strength, high-temperature-resistant inorganic coating, characterized in that: The inorganic coating comprises the following raw materials in parts by weight: 20~40 parts of dimensional filler 1~15 parts of thermal insulation filler 30~40 parts of silicate 5 to 20 parts of metal oxide, and 90~150 parts of silica sol.

2. The inorganic coating according to claim 1, characterized in that The mass ratio of the silicate to alumina is 2-6:1, and the mass ratio of the silicate to silica sol is 1:2.5-4.

2.

3. The inorganic coating according to claim 1, characterized in that The dimensional filler includes one or more of mullite fiber, chopped quartz fiber powder or chopped glass fiber powder.

4. The inorganic coating according to claim 1, characterized in that The particle size of the dimensional filler is 10-50 um.

5. The inorganic coating according to claim 1, characterized in that: The heat insulating filler includes one or more of expanded perlite, expanded vermiculite, hollow glass microspheres, hollow phenolic microspheres or silica aerogel.

6. The inorganic coating according to claim 1, characterized in that: The thermal insulation filler has a density of 0.2-0.6 g / cm³, a compressive strength of 10-55 MPa, and an average particle size of 10-50 um.

7. The inorganic coating according to claim 1, characterized in that The purity of the metal oxide is above 99wt% and the particle size is 10-50um.

8. The inorganic coating according to claim 1, characterized in that: The metal oxide includes one or more of aluminum oxide, magnesium oxide or zirconium oxide.

9. A method for using the inorganic coating according to any one of claims 1 to 8, characterized in that: The method of use comprises: mixing the materials in proportion, stirring them evenly and then coating them on the surface of an object; after the coating is cured, heating them at 600° C. to 800° C. for 1 to 3 hours to obtain a high-strength and high-temperature resistant inorganic coating.

10. A method of use according to claim 9, characterized in that: The coating curing temperature is 20° C. to 60° C., the curing time is 18 h to 30 h, and the thickness of each coating layer is 0.8 mm to 1.5 mm.

Citation Information

Patent Citations

  • Fiber-reinforced high-temperature-resistant thermal insulation and heat preserving ceramic coating and preparation method thereof

    CN102464933A

  • Nano porous thermal insulation material matrix surface high-temperature-resistant coating and preparation method thereof, and matrix

    CN111217620A

  • High-temperature-resistant coating and preparation method thereof

    CN116925581A

  • A seramic heat resistance and themal insulation paint

    KR102517431B1

  • Ceramic coating on metal

    US4950627A